The Direction of Research in the Field of Strategic Management in the Face of Contemporary Challenges - Kafel, Tomasz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The aim of this study was to present the development of the schools of strategic management and the diffusion of selected approaches to strategic management in Polish companies, as well as to determine the future direction of scientific research in this field. The study was based on research conducted by a team of researchers from the University of Economics in Poznań in 2010. The challenges faced by practitioners and theorists who have taken up the issue of strategic management are presented based on the analysis of domestic and foreign literature. The consequences of these challenges for the process of strategic management and the directions for further research in this field are set out.